Application of elastic metamaterials/meta-structures in civil engineering: A review - Contreres, Nicolas; Zhang, Xihong; Hao, Hong; Hernández, Francisco (Elsevier, 2024)
Inspired by sonic engineering, locally resonant metamaterials have attracted much attention from researchers in civil engineering for their unique characteristics of stress wave attenuation and vibration control capacities. This paper presents a comprehensive review of the latest progress of locally resonant metamaterials and their potential applications in civil engineering for structure protection against dynamic loads. The concepts of metamaterials for stress wave attenuation are introduced first, followed by a comprehensive overview of the historical origins and development of metamaterials. Existing analytical approaches for metamaterials, including theoretical solutions, numerical simulations, and experimental examinations, are summarised. Commonly used meta-structures with internal or external resonators and their applications are reviewed and discussed. Research gaps and future outlooks are also identified and briefed.